Mullah Omar's death Pakistan's role in Afghanistan - Halimullah, Kousary (2015)
With western forces out of Afghanistan, Pakistan fears Taliban winning exclusive power in Afghanistan and thus tries to facilitate a power sharing deal between Taliban and the Afghan government. Mullah Omar's death is a factor behind this persuit.